Evaluation of the antioxidant and endothelial protective effects of Lysimachia christinae Hance (Jin Qian Cao) extract fractions - Ning-hua Wu; Zhi-qiang Ke; Shan Wu; Xiao-song Yang; Qing-jie Chen; Sheng-tang Huang; Chao Liu (BMC, 2018)
Abstract Background Lysimachia christinae Hance is a traditional Chinese medicine with diuretic, detumescent, and detoxifying effects. Our aimed to optimize the extraction protocol to maximize the yield of flavonoids from Lysimachia christinae Hance, and evaluate the pharmacological activities of four fractions, namely, petroleum ether (PE), ethyl acetate (EA), n-butanol (NB), and aqueous (AQ) fractions, of the ethanolic extract of Lysimachia christinae Hance. Methods The flavonoid monomers in the crude extract were characterized via high performance liquid chromatography (HPLC), were used as markers for extract quality control and standardization. The total flavonoid, total phenolic, and total polysaccharide contents of each fraction were determined by spectrophotometry. Further, the in vitro free radical (diphenylpicrylhydrazyl, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid), superoxide, and hydroxyl radicals) scavenging activities, and antioxidant capacity in endothelial cells were evaluated for each fraction. Results After optimizing the extraction protocol to maximize the total flavonoid yield from L. christinae Hance, the NB fractions had the highest total flavonoid (39.4 ± 4.55 mg RE/g), total phenolic (41.1 ± 3.07 mg GAE/g) and total polysaccharide (168.1 ± 7.07 mg GE/g); In addition, the NB fraction of the ethanolic extract of L. christinae Hance reveal the strongest radical-scavenging activity, antioxidant activity and protective effects against H2O2-induced injury in HUVECs. Conclusions Among the four fractions of L. christinae Hance, the NB fraction showed the most potent antioxidant and endothelial protective effects, which may be attributed to its high flavonoid, phenolic contents and optimal portfolio of different active ingredients of NB fractions of the ethanolic extract of L. christinae Hance. This study might improve our understanding of the pharmacological activities of L. christinae Hance, thereby facilitating its use in disease prevention and treatment.